« first day (582 days earlier)      last day (1607 days later) » 
05:00 - 13:0013:00 - 18:00

1:00 PM
OK, let me.
If 5= 0 then 2^5= 1, otherwise 2^5 = 2^(5-1)·2
OK if 2=0,then 2^4=1 otherwise 2^4=2^(4-1).2
And if 3=0 then 2^3=1 otherwise 2^3=2^(3-1).2
If 2=0 then 2^2=1 otherwise 2^2=2^(2-1).2
If 1=0 then 2^1 otherwise 2^1=2^(1-1).2
There was a typo in second.
@user21820
 
Okay. The original was correct. I don't know why you edited it.
Is that all?
 
Yes.
 
No, you need one more.
Your last one above gives you 2^1 = 2^0·2.
That is not enough to finish.
 
For 2^0
0=0 for each 0,then 2^0=1
 
What is "for each 0"??
What happened to your copy and paste?
 
1:08 PM
I am using my dad old smart phone.
Which has broken screen.
 
Alright.
Still, I need to see that you actually get it right.
So fix your attempt.
 
If 0=0 then 2^0=1.
 
Good.
Now that you have done it, here is mine. You can see how being systematic makes everything clearer.
If 5 = 0 then 2^5 = 1, otherwise 2^5 = 2^(5−1)·2. 5 ≠ 0. So 2^5 = 2^4·2.
If 4 = 0 then 2^4 = 1, otherwise 2^4 = 2^(4−1)·2. 4 ≠ 0. So 2^4 = 2^3·2.
If 3 = 0 then 2^3 = 1, otherwise 2^3 = 2^(3−1)·2. 3 ≠ 0. So 2^3 = 2^2·2.
If 2 = 0 then 2^2 = 1, otherwise 2^2 = 2^(2−1)·2. 2 ≠ 0. So 2^2 = 2^1·2.
If 1 = 0 then 2^1 = 1, otherwise 2^1 = 2^(1−1)·2. 1 ≠ 0. So 2^1 = 2^0·2.
If 0 = 0 then 2^0 = 1, otherwise 2^0 = 2^(0−1)·2. 0 = 0. So 2^0 = 1.
 
All done by definition^
 
Last one look stupid because in detention we already said m^n=1 for n=0
Then why we need otherwise.
 
1:11 PM
@yuvrajsingh What you are told in detention may or may not be correct. But what I told you is the true mathematical definition.
It covers all cases. Look carefully at what I just wrote above to see how the definition I gave you fully controls the meaning of 2^5.
Tell me, by the definition, what is 0^0?
 
What next, my question?
 
0 = 0 is the only true statement, right?
 
It is undefined? @user21820
 
Wrong.
Apply my definition.
 
I am writing but still I am on my words 0^0=1
 
1:15 PM
replace "2" with "0" please :-)
 
If 0=0 then 0^0=1 other wise 0^0=0^(0-1).0
 
Right. So the point is that by the definition I gave you 0^0 = 1. I don't care what any other teacher says, because you must understand that this 100% precise definition states that 0^0 = 1.
And if you ask any professional logician they will agree with my definition.
Now I want you to understand one more thing, before we get back to your "a^b^c" question.
 
Yes?
 
Observe that when you apply the definition to any specific naturals m,n, such as 2 and 5 in the above example, the definition can be expanded 'all the way to the bottom'.
This is what I meant earlier by saying:
3 hours ago, by user21820
I write it this way to make it clear that the definition is well-founded, meaning that it is not circular. Indeed, you can for any m,n expand the definition of m^n all the way until it 'terminates' at the base case.
Do you understand this? This is a non-trivial issue that you must understand if you want to understand definitions in general.
 
Understand.
But what the word trivial means.
Or non trival means.
 
1:20 PM
Good. In the future, you might see in textbooks that such definitions are called "recursive definitions" or "inductive definitions". "Trivial" means "insignificant/small". "Non-trivial issue" means "important".
Right now you do not need to know why they are called "recursive" or "inductive", but if you know programming then I can explain it to you.
 
So what we mean when we say solution is trival.
In mathematics.
 
It means it is some easy-to-find solution
 
OK.
@user21820 continue.
 
Now back to "a^b^c". This is ambiguous, because you must specify whether you mean (a^b)^c or a^(b^c).
 
Second one.
 
1:23 PM
You asked about "128^128^128", and later specified "(128^128)^128". I said that it makes no sense, because there is a basic property regarding (a^b)^c.
Right, now you are saying you actually wanted 128^(128^128).
 
Yes.
 
You also incorrectly reduced the exponentiation, because you wrote:
6 hours ago, by yuvraj singh
So I write the above part as $(64)^2(64)^2(64^2)
I really have no idea what it means, but it is surely wrong.
Remember, 128^128 is defined exactly as I showed you above, which expands to 128 copies of 128 multiplied together.
2·3^4 is not the same as (2·3)^4.
 
I admit.
 
Okay so the question is what is the remainder of 128^(128^128) when divided by 3.
In programming terms, you want 128^(128^128) mod 3.
Are you familiar with "mod"?
 
1:28 PM
Okay then we build everything from scratch.
For convenience, let k = 128^128. We want remainder of 128^k when divided by 3.
 
The phrase "a mod b" is defined to mean "the remainder of a when divided by b".
Save us time writing.
Now, do you agree that (a+b) mod b = a mod b, for any integers a,b where b > 0?
 
Yes.
 
Do you agree that (a+b·c) mod b = a mod b, for any integers a,b,c where b > 0?
 
1:32 PM
Using this fact, can you simplify (a+b)·c mod b?
(Here "·" has higher precedence than "mod".)
 
What do you get?
In case it is not clear, I'm asking you to fill the blank something simple:
> (a+b)·c mod b = _______, for any integers a,b,c where b > 0.
I'll be back later. Take your time, and then do the same for:
 
a mod b. +c
 
> (a+b·d)·c mod b = _______, for any integers a,b,c,d where b > 0.
@yuvrajsingh No guessing. Guesses are almost always wrong, especially when you lack mathematical experience.
Use only the facts I have listed above.
 
No I haven't guess.
I am honest.
 
1:40 PM
Then provide the calculation using the facts.
I will be back later.
 
Are you going, how much time?
@user21820
 
1:55 PM
So answering the first one.
 
2:23 PM
@yuvrajsingh I'm back, but I don't see your answer..
 
OK.
(a+b). c/b.
So we get a mod b +c mod b @user21820
 
I don't know what you mean.
 
?.
Sorry. I rewrite them.
 
In mathematics, you should write only true statements.
"1+1 = 2" is a true statement. "1+1" is not a statement.
What you wrote is not a statement, so I don't even know what you're claiming.
(And your final answer is wrong, so you definitely made a mistake somewhere.)
 
2:40 PM
@yuvrajsingh: If you cannot get it, I can give you a hint.
 
No I will try.
(a+b). c mod b.
Which implies remainder of (a+b). c when divided by b.
So answer is a mode b +c.
@user21820
 
No as I said, that answer is wrong.
 
No sir.
Let me write it again.
a mod b+1 @user21820 it is not a guess.
 
"a mod b + c" is wrong.
In mathematics, you cannot make any jump in thinking. You must be able to systematically obtain facts based on previous ones, without relying on intuition or guessing. You went straight from "remainder of (a+b)·c when divided by b" to "a mod b + c", without justification.
Err... in my viewpoint, anything that does not have solid logical justification is a guess.
 
@user21820 if my answer is correct, then I have write to justify it. So is my answer correct?
 
2:51 PM
No it is wrong. I said three times already that it is wrong.
 
I can, t find where I am getting wrong?
 
You can test small numbers to check your own claim. Your claim is that (a+b)·c mod b = a mod b + c. Try substituting c = 1 and seeing whether that contradicts what you previously agreed with.
 
My answer is wrong.
How stupid I am.
Or I just lost my sense?
@user21820
 
No you just made a mistake.
Let me show you how to start.
 
2:58 PM
(a+b)·c mod b = (a·c+b·c) mod b = ... Can you finish, using the previous facts?
 
ac mod b +bc mod b.
 
It's more or less correct, but not quite. 1 mod 3 + 2 mod 3 = 1 + 2 = 3. (1+2) mod 3 = 3 mod 3 = 0.
Why don't you just use the previous facts?
1 hour ago, by user21820
Do you agree that (a+b·c) mod b = a mod b, for any integers a,b,c where b > 0?
 
Oo so ac mod b.
 
Right.
So let's write it again.
> (a+b)·c mod b = (a·c) mod b for any integers a,b,c where b > 0.
1 hour ago, by user21820
> (a+b·d)·c mod b = _______, for any integers a,b,c,d where b > 0.
What about the next one?
 
ac mod b
 
3:05 PM
Right again.
If you notice, I try to be careful to always state the conditions under which my statements apply. You also should try.
This is how to be mathematically precise. What works under some conditions may not work under other conditions.
Now back to mod.
 
One question from the last?
 
The last fact we went through shows that if you have a product "x·y mod b", you can take away any multiple of b from x and it would remain the same.
@yuvrajsingh Go ahead.
 
How bcd mod b become zero.
 
b·cd is a multiple of b.
Are you satisfied with the facts so far?
 
Yes.
Can go to have some water.
 
3:11 PM
Sure.
When you're back, is it clear that 8·8 mod 3 = 2·8 mod 3 = 2·2 mod 3?
How about 8·8·8 mod 3?
How about 8^n mod 3, for natural n?
 
3:26 PM
First is 3.
For second I can write (9-1)
So remainder be 1.
@user21820
 
I don't get your answers.
 
Why?.
 
As I said before, when you do not write a statement, it is unclear what you are claiming. And besides, what you write has nothing to do with the answer.
Write true statements.
At least write statements, so that I can give counter-examples to disprove them.
 
Sorry, I promise I won, t make this mistake again.
For first are you asking the value or like this When you're back, is it clear that 8·8 mod 3 = 2·8 mod 3 = 2·2 mod 3?
@user21820
 
@yuvrajsingh Yes, and your answer should be "yes" or "no". If it is "yes" then you should be able to explain how to obtain this result from the above facts.
 
3:39 PM
My eye is painting can I take a break for an hour. @user21820
 
@yuvrajsingh You can take a much longer break, as I will need to go soon. =)
Basically, you just have to find suitable substitutions to use the above fact:
 
Sorry if you get. Angry.
 
> (a+b·d)·c mod b = a·c mod b, for any integers a,b,c,d where b > 0.
Take your time to find those substitutions to show that 8·8 mod 3 = 2·8 mod 3 = 2·2 mod 3.
 
Got it can I answer.
 
And then think how you can use the same technique to simplify 8·8·8 mod 3, and in general 8^n mod 3.
 
3:42 PM
Yes.
 
Also think about 8·8 mod 3 = (−1)·(−1) mod 3.
That's all I have for you for now. See you another day!
 
64.8 mod 3, and (2+30.2) mod 3 is it right @user21820
Or (2+20.3)mod 3
 
I think you should take a break. I can't understand you, and probably you won't understand yourself after you come back to what you just wrote. Bye!
(Mathematics should not be rushed.)
 
OK. Bye.
 
4:15 PM
(4+30.2).8,mod 3 can be thia similar to (a+bc).d mod b @user21820
 
@yuvrajsingh Yes so what is the statement that you get?
 
Actually I was writing this only.
32 mod 3.=2
 
But you're not using the same technique. You immediately computed 8·8 = 64. It is correct, but you cannot generalize your method to 8^n.
You need to try to do exactly the same as I did with 8·8 mod 3, but now with 8·8·8 mod 3.
More 8s, but same trick.
 
8^n can be (9-1)^n.
 
Yes, and then what? I want to see you do 8·8·8 mod 3 correctly first.
@yuvrajsingh And avoid imprecise language like "can be". 8^n = (9−1)^n.
 
4:20 PM
OK.
8.8.8.mod 3 is 8.2.8mod 3=2.2.8mod 3=2.2.2mod3=8mod3
=2
@user21820
 
Good good.
Do the same trick, but using 8 = 9−1.
So that you can handle 8^n mod 3 easily.
Same for 128^n.
 
That will get me to (9-1)mod 3.
-1mod 3
That will be equal to 2.if power n will not be there.
2^n will be the remainder @user21820
 
Third time I'm telling you to write statements. Nothing you just wrote is a statement.
I cannot accurately assess whether you are correct if you don't write full statements.
 
8^mod 3=(9-1)^n mod 3=-1^n mod 3=2^n.@user21820
 
4:35 PM
Excellent. It is all correct (except missing brackets). But notice that you don't actually want the last equality!
 
"−1^n" in mathematics is always interpreted as "−(1^n)" because of precedence rules. So that is not what you should have written.
Write it again with the correct brackets, and don't go to "= 2^n mod 3", and think of another easier final step.
 
- (1^n)mod 3.
 
I suspect you have problems with arithmetic...
Substitute exactly into the above facts, if you want to ensure correctness.
 
-(3-2)^n mod 3
 
4:41 PM
No. That's why I asked you to do the following first:
58 mins ago, by user21820
Also think about 8·8 mod 3 = (−1)·(−1) mod 3.
You did not do it. And your guessing is incorrect.
 
What wrong in that I get 2^n mod 39
I haven't guess, and I assure, in the example you have given.
 
You wrote "(9-1)^n mod 3=-1^n mod 3". That is wrong. You later wrote "-(1^n)mod 3" with no statement. Also wrong.
 
OK so I should write statement. Yes?
 
Yes, and do the simple example 8·8 mod 3 = (−1)·(−1) mod 3 first using the fact.
And then repeat for 8^n mod 3.
 
8^n mod 3=(9-1)^n mod 3=-(1^n)mod 3=-(3-2)^n mod 3=2^n mod 3.
 
4:47 PM
I asked you to use the fact by exact substitution. You are not following instructions again.
 
8.8mod 3=8.(3.2+2)mod 3=2.2 mod 3.
 
1 hour ago, by user21820
> (a+b·d)·c mod b = a·c mod b, for any integers a,b,c,d where b > 0.
@yuvrajsingh Yes that is right, to get 8·8 mod 3 = 2·2 mod 3.
But you did not do it right for the other one.
So do the actual substitution!
 
Got it.
 
That is what I mean by "you guessed", because you guessed how it would turn out without actually manually doing the substitution.
 
8^n mod 3=(3.2+2)^n mod 3=2^n mod 3.
@user21820
 
4:52 PM
That is correct, but I also asked you to do...
1 hour ago, by user21820
Also think about 8·8 mod 3 = (−1)·(−1) mod 3.
 
I already did it 2 times and you said OK too?
 
Nothing in what you wrote includes "(−1)·(−1) mod 3."!!
Don't you see a big fat negative one?!
 
OK (3.3-1)(3.3-1) mod 3=(-1)(-1)mod 3
@user21820
 
Aha finally. Though you should have written "(3·3+(−1))", otherwise it is not exactly a rigorous use of the fact.
Now simplify 8^n mod 3 using the same technique.
 
(3.3+(-1))^n mod 3=-(1) ^n mod 3 -(3-2)^n mod 3=2^n mod 3.
@user21820
 
5:02 PM
Wrong.
 
Now what?
 
Don't anyhow move brackets wherever you like. Substitute properly.
 
I haven, t put any extra Bracket.
 
Look, you clearly have a problem with basic arithmetic. One way to avoid your very frequent arithmetic errors is to substitute exactly carefully. Copy-paste the following fact and substitute each variable with the exact same expression.
1 hour ago, by user21820
> (a+b·d)·c mod b = a·c mod b, for any integers a,b,c,d where b > 0.
 
As I said I am not using PC, I have old broken screen phone.
 
5:06 PM
You can manually copy-paste. You don't have a choice, because you are making these basic errors that you shouldn't be making.
 
((−1)+3·3)·8 mod 3 = ...
 
From next time, I won, t make this error promise.
Next?
 
1 min ago, by user21820
((−1)+3·3)·8 mod 3 = ...
Maybe you didn't read what I wrote properly:
34 mins ago, by user21820
"−1^n" in mathematics is always interpreted as "−(1^n)" because of precedence rules. So that is not what you should have written.
 
((−1)+3·3)^n. 8 mod 3 = ...-(3+(-2))^n mod 3=2^n mod 3.
 
5:13 PM
I can't believe that you still do not follow instructions. Why waste our time with typing so many other wrong things, instead of copying exactly and substituting?
For the last time, I ask you to substitute the a,b,c,d in "(a+b·d)·c mod b = a·c mod b" with appropriate values to get "((−1)+3·3)·8 mod 3 = ...". Fill it in.
 
05:00 - 13:0013:00 - 18:00

« first day (582 days earlier)      last day (1607 days later) »